Compressive Strength of Cement Mortar blended with Coconut Fibers and Human Hair - Ibrar Ahmad; Fayaz Ahmad; Shah Room; Zubair Abdullah; Muhammad Ihsan (Advances in Science, Technology and Engineering Systems Journal, 2016)
Mortar is used all over the world for construction purpose. It consists of cement paste and fine aggregates and admixtures if required are also incorporated to modify some of its properties. In this study coconut fibers and human hair were used as an additive materials in the mortar and its effects on compressive strength of the mortar were investigated. Coconut fibers and human hair are waste materials which are produced in millions of tons every year which create not only biodegradability problems but also cause pollution. Coconut fibers and human hair were used as additive materials in mortar in 2, 4 and 6 % to prepare blended mortar. Mortar samples of coconut fibers and human hair were prepared and compared with each other and control samples. Cement to sand ratio was kept 1:3 with water cement ratio of 0.6 for all mixes. Cubes having dimensions of 2×2×2 inches were used in this project. All the mixes were cured at normal room temperature for 3, 7 and 28 days. Results revealed that mix with 4% coconut fibers showed higher compressive strength at 3 days and 6% higher compressive strength at 28 days. With increase of coconut fibers compressive strength increased. However, mortar with human hair initially shows higher strength when 2 % was incorporated but with increasing percentage of human hair, strength was reduced. With addition of mix fibers i.e. coconut fibers and human hair into the mix, the compressive strength initially increased at 3rd day of curing, showing higher compressive strength at 3 days for all percentages of mix compare to reference mortar, however with further increase of percentage of mix fibers into the mortar, the compressive strength was reduced showing lowest compressive strength at 28th days for 4% of mix fibers i.e. coconut fibers and human hair.
Keywords: Fibers; Pollution; Blended Mortar